Sink cities and land subsidences: How it affects the development of coastal city in Malaysia? - Nur Hasnieda Zawawi; Norzailawati Mohd Noor; Chaabane, Ferdaous (Penerbit Universiti Kebangsaan Malaysia, 2023)
Land subsidence is the process through which the surface of the Earth gradually sinks or suddenly sinks due to the movement of earth components occurring below the surface. Subsidence can occur suddenly or gradually. The impacts of permanent inundation, which might make the environment of the settlement area worse, will raise the risks and challenges that the population will face in the future. These risks and challenges may include things like natural disasters and economic instability. This is true especially because cities that are inundated will enhance the dangers and difficulties that the population would have to face. The objective of this article is to provide a comprehensive overview and systematic literature on sink cities and land subsidence and how it affects the development of coastal cities in Malaysia. It examines how development contributes to land subsidence and sink cities in coastal area. According to the findings, cities in various countries, including Malaysia, have been affected by land subsidence. Based on the research, cities, and land in countries like Indonesia, Bangladesh, and Vietnam are sinking due to land subsidence. As a result of land subsidence, changes in land use have occurred, the most noticeable of which are those associated with the erection of structures and residential areas in the coastal zone. The findings indicate that Malaysia is one of a select number of nations where sinking cities and land subsidence occur. Seawalls, breakwaters, gabions, groynes, and sluices are some of the potential solutions to the problems created by subsiding land and sinking cities. The purpose of these regulations is to forestall the development of "sink cities".